Pengaruh Kesejahteraan Karyawan, Motivasi Dan Keterampilan Terhadap Produktifitas Kerja - Manorek, Sutria Langling (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This type of research is qualitative research using linear regression data analysis techniques. The population in this study is that all permanent employees at PT Bank SulutGo in Manado region, as many as 1,276 and drawn samples using the Slovin formula to 150 respondents.The test results show that Employee Welfare, Motivation and Skills together have a positive and significant effect on Work Productivity, Employee Welfare and Motivation partially influential on Employee Work Productivity while Skills do not affect Employee Work Productivity at PT Bank SulutGo ManadoKeywords: Employee Welfare, Motivation, Skills and Work Productivity